Co‐inheritance of HNF1a and GCK mutations in a family with maturity‐onset diabetes of the young (MODY): implications for genetic testing. (1st April 2013) - López‐Garrido, M. P.; Herranz‐Antolín, S.; Alija‐Merillas, M. J.; Giralt, P.; Escribano, J.
Summary Objective To determine the genetic basis of dominant early‐onset diabetes mellitus in two families. Patients and methods Molecular analysis by PCR sequencing of the promoter, the 5′ untranslated region (UTR) and exons of both GCK and HNF1A genes was carried out in two families with clinically diagnosed dominant diabetes mellitus. Results The novel HNF1A c.‐154_‐160TGGGGGT mutation, located in the 5′ UTR, was present in several members of the two families in the heterozygous state. Interestingly, the GCK p.Y61X mutation was also identified in three members of one of the families, and two of them carried both mutations in heterozygosis. To the best of our knowledge, this is the first report of the co‐inheritance of GCK and HNF1A mutations and the coexistence of maturity‐onset diabetes of the young (MODY) 2, MODY 3 and unusual MODY 2–3 genotypes in the same family. Conclusions Carriers of both GCK and HNF1A mutations manifested a typical MODY 3 phenotype and showed that the presence of a second mutation in the GCK gene apparently did not modify the clinical outcome, at least at the time of this study. Our data show that co‐inheritance of MODY 2 and MODY 3 mutations should be considered, at least in some cases, for accurate genetic testing.